2005
DOI: 10.1088/0967-3334/26/6/011
|View full text |Cite
|
Sign up to set email alerts
|

The clinical application of non-invasive intracranial blood volume pulse wave monitoring

Abstract: An ultrasonic method was used to non-invasively measure intracranial blood volume (IBV) pulse waveforms. This technology has previously shown a strong association between invasively recorded ICP pulse waves and non-invasively recorded IBV pulse waves. The objective of the present study was to investigate the diagnostic value of non-invasively measured IBV pulse waves in the cases of different pathologies. A total of 75 patients were examined and these included cases of acute, chronic and stabilized hydrocephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Success has previously been reported in quantifying relative CBV noninvasively with an ultrasound time-of-flight measurement. 20 This measurement was then used to measure vascular reactivity as a phase shift between the relative blood volume and the ABP changes at the respiratory frequency as opposed to analyzing at the frequency of slow waves as is done with the PRx and the HVx. 6 The theoretical advantage of using respiratory frequency waveform analysis is the regular periodicity when compared with the sporadic nature of slow waves.…”
Section: Discussionmentioning
confidence: 99%
“…Success has previously been reported in quantifying relative CBV noninvasively with an ultrasound time-of-flight measurement. 20 This measurement was then used to measure vascular reactivity as a phase shift between the relative blood volume and the ABP changes at the respiratory frequency as opposed to analyzing at the frequency of slow waves as is done with the PRx and the HVx. 6 The theoretical advantage of using respiratory frequency waveform analysis is the regular periodicity when compared with the sporadic nature of slow waves.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that results can be obtained which are similar to MRI technology by using the non-invasive ultrasonic method for intracranial blood volume pulse wave (IBVPW) measurement (Ragauskas and Daubaris, 1995;Ragauskas et al, -2004Deltuva, 1999;Matukevicius, 2000;Rocka, 2003;Ragaisis, 2003;Kvascevicius, 2003;Kalasauskas, 2003;Chambers et al, 2005;Fountas et al, 2005). The method has been tested using simultaneous invasive ICP and non-invasive IBV wave monitoring of TBI patients.…”
Section: Introductionmentioning
confidence: 80%
“…A-9676. The analysis involved 87 hours of simultaneous monitoring of invasive and non-invasive data (Ragaisis, 2003;Chambers et al, 2005). The diagnostic value of IBV pulse waves has been investigated in previous studies (Ragauskas et al, -2004Rocka, 2003;Kvascevicius, 2003;Kalasauskas, 2003;Fountas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors focused on the devices and mathematical approach of tomography impedance of the head [18, 19]. Besides measuring electrical impedance, other devices have been proposed to assess the intracranial blood volume based on the time-of-flight of short ultrasonic pulses from one side of the skull to the other [20]. …”
Section: Introductionmentioning
confidence: 99%